Assessment of Ground Water Quality of Ghazipur District, Eastern Uttar Pradesh, India, Special Reference to Arsenic Contamination - Amit Pal, Rajesh Singh, Dadhibal Prasad Gond (Recent Research in Science and Technology, 2010)
Now a days water quality has solicited a major global concern due to ever increasing human developmental activities that over exploit and pollute the water resources on surface and underground. Situation is very worst in developing as well as developed nations. In this context the status of water quality of Gazhipur district of Eastern Uttar Pradesh of India was carried out for the present study to identify the arsenic contamination of ground water. Arsenic contamination in ground water in India was first identified in lower Ganga plain of West Bengal later on Bihar, Jharkhand and also apprehended in Uttar Pradesh. Keeping the view to arsenic contamination in adjacent district Ballia, the present investigation therefore has been undertaken the possible arsenic contamination in and around Ghazipur district of eastern Uttar Pradesh.